Bypass Surgery for Complex Intracranial Aneurysms: 15 Years of Experience at a Single Institution and Review of Pertinent Literature. Issue 6 (14th June 2017) - Ban, Seung Pil; Cho, Won-Sang; Kim, Jeong Eun; Kim, Chang Hyeun; Bang, Jae Seung; Son, Young-Je; Kang, Hyun-Seung; Kwon, O-Ki; Oh, Chang Wan; Han, Moon Hee
Abstract: BACKGROUND: Bypass surgery is a treatment option for complex intracranial aneurysms. OBJECTIVE: To determine the utility of bypass surgery for the treatment of complex intracranial aneurysms and to review the literature on this topic. METHODS: Sixty-two patients were included in this retrospective study. Unruptured aneurysms were dominant (80.6%), and the internal carotid artery was the most common location of the aneurysm (56.4%), followed by the middle cerebral artery (21.0%). The mean maximal diameter of the aneurysms was 20.5 ± 11.4 mm. The clinical and angiographic states were evaluated preoperatively, immediately after surgery (within 3 days) and at the last follow-up. The mean angiographic and clinical follow-up duration was 34.2 ± 38.9 and 46.5 ± 42.5 months, respectively. RESULTS: Sixty-one patients (98.3%) underwent extracranial–intracranial bypass, and 1 underwent intracranial–intracranial bypass. At the last follow-up angiography, 58 aneurysms (93.5%) were completely obliterated and 4 were incompletely obliterated, with a graft patency of 90.3%. Surgical mortality was 0 and permanent morbidity was 8.1%. A good clinical outcome (Karnofsky Performance Scale ≥ 70 and modified Rankin Scale score ≤ 2) was achieved in 91.9% of patients (n = 57). CONCLUSION: With a proper selection of bypass type, bypass-associated treatment can be a good alternative for patients with complex intracranial aneurysms when conventional microsurgical clipping or endovascular intervention is not feasible.